Green synthesis and antibacterial evaluation of some 2-pyrazoline derivatives - Santhi, N.; Emayavaramban, M.; Gopi, C.; Manivannan, C.; Raguraman, A. (International Journal of Advanced Chemistry, 2014)
A Chalcone (3) was prepared by the reaction of 4-methylbenzaldehyde (1) with 4-methylacetophenone (2) in methanolic sodium hydroxide result under ultrasonic irradiation in the water bath of a ultrasonic cleaner at room temperature. Treatment of this chalcone with thiosemicarbazide / semicarbazide hydrochloride / benzhydrazide / benzenesulphonyl hydrazide / phenylhydrazine hydrochloride managed the comparing 2-pyrazoline (4-8) in great yields. All the new mixes have been described by IR, 1H-NMR, 13CNMR ghostly information. All the target mixes were assessed for their in-vitro against antifungal in examination with as reference pill.   Keywords: 4-Methylbenzaldehyde, 4-Methyl Acetophenone, Ultrasonic Irradiation, Chalcone, 2-Pyrazoline, Antibacterial.